(3MOjK GHf cTejQs - (3GHf cTejQs ((3eMeO Hf eMeO Ydi s)
(3ChdgG (B:s
(3Qhi YHO Gddg GdeOGjfi hcGfJ cdeJi hcdeg hGMOI MJi Gfg de jcf jNai Yfi TjFkG ef CehQg s
(3BNQgG (B:s
(3hSQJ MJi CJjJ GdchaI adeG ONdJgG YeOJ Edi eGFI OjfGQ ahgHJgG ddCShOjf abdJ CfJeG MQGf dhLg Gddg JYGdi heQJ MJi ONdJ HZOGO hgPG eG cGf ef MOjKi hUdi Gddg Ydi eMeO hBdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs